Philosophical Critique of Capital Market Regulation: A Case Study between Public Interest and Privacy - Enos Martryn Budiman (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2026)
Purpose: This study aims to analyze capital market regulation through the lens of philosophical principles to evaluate the balance between transparency for the public interest and the protection of individual privacy rights in achieving justice. Methodology/Approach: This research adopts a normative legal method supported by conceptual and philosophical approaches. The study analyzes primary legal instruments, secondary literature, and tertiary references through qualitative library research to examine regulatory tensions between transparency and privacy in Indonesia’s capital market governance. Results/Findings: The findings show that Rawlsian justice, Kantian autonomy, and utilitarian ethics are useful frameworks for evaluating the ethics of capital market regulation. Although Indonesia’s Capital Market Law and OJK regulations emphasize transparency, investor data privacy remains inadequately protected. Adopting stronger data protection standards, such as the GDPR, alongside local principles of maslahah and subsidiarity, can enhance regulatory fairness and reduce burdens on small market participants. Conclusions: The study concludes that harmonizing transparency and privacy requires risk-based, ethically informed reforms that are responsive to technological changes. Strengthening the integration between capital market law and personal data protection is essential for creating a more just and sustainable regulatory framework. Limitations: This research is limited to theoretical-normative analysis and focuses primarily on the Indonesian legal context, which may affect its broader applicability. Contribution: The study contributes to the intersection of legal philosophy, capital market regulation, and data governance by proposing a value-based framework for balancing transparency and privacy. Its implications are particularly relevant for lawmakers, regulators, and legal scholars in emerging economies.